Development policy: new thinking about an interpretation - Healey, D. I. (Journal of Economic Literature, 1972)
IT IS CURious how in scientific disciplines very similar results of investigations into problems appear to emerge at the same time. It is as if the essential reality of a situation comes into increasing conflict with accepted ideas until, at a certain point, reality cannot be gainsaid. From various quarters attacks begin to mount and we begin to wonder why we were so simple-minded as to accept uncritically earlier concepts. Even so, we do not lightly reject these other views because, after all, a good deal of intellectual energy has gone into their formulation and propagation. We wait to be convinced; each new, available piece of research is scanned to see whether it supports the tenets of the old doctrine, or whether it adds to the growing swell of disillusionment. Finally, if we are honest, we are forced to admit that reality has not been explained by our older notions-there are too many discrepancies between facts and theory-and we embrace the new approach. These reflections are engendered upon reading three books published at the end of 1970 or the beginning of 1971.1 All deal with the results of many years of development efforts by developing countries and all are critical of present policies. Broadly speaking, we may say that the LittleScitovsky-Scott book concentrates its criticisms on policies of import-substittiton whilst the ILO and Turnham books focus upon the failure of policies to obviate growing unemployment. Let us look at the Little-Scitovsky-Scott book first. This is an interesting example of what can be achieved by teamwork in economic research. The book was based on researches undertaken in various countries (Brazil, India, Pakistan, Mexico, Philippines, and Taiwan) by those who had extensive knowledge of the countries concerned. Their individual contributions were analyzed by the three authors (who also incorporated material on Argentina). The result is a well-documented multiple casestudy of development, with theoretical iinplications far beyond the particular countries covered.2 Little-Scitovsky-Scott3 concern themselves first with a consideration of the factors which have led to the growth of import-substitution. One factor was the de-